Spotlight on COVID‐19: eighteen months on. (6th September 2021) - Zacchigna, Serena; Marcello, Alessandro; Banks, Lawrence
Abstract : In this Editorial, we highlight the contents of The FEBS Journal 's second Special Issue focussed on COVID‐19. The issue covers a variety of aspects related to COVID‐19, ranging from the most recent improvements in therapies and the significant impact of rapidly developed COVID‐19 vaccines to the emergence of variants of SARS‐CoV‐2, the role of the immune system in the various stages of the disease and the impact of the disease in different organs. We hope that this collection of articles will give readers an informative and critical perspective on recent advances in understanding and treating COVID‐19. Abstract : In this Editorial, Lawrence Banks and co‐authors highlight the contents of The FEBS Journal 's second Special Issue focused on COVID‐19. The issue covers a variety of aspects related to COVID‐19, ranging from the most recent improvements in therapies and the significant impact of rapidly developed COVID‐19 vaccines, to the emergence of variants of SARS‐CoV‐2, the role of the immune system in the various stages of the disease and the impact of the disease in different organs. We hope that this collection of articles will give readers an informative and critical perspective on recent advances in understanding and treating COVID‐19.